DemoGravity: World Population and Trade in the 21st Century - Steven Brakman; Tristan Kohl; Charles van Marewijk (CESifo GmbH, 2024)
The availability and composition of labor is fundamental for the structure of international trade. This points towards the importance of demographic transitions that affect trade through, for example, changing capital-labor ratios, urbanization dynamics, or changes in the composition of demand over the life cycle of individuals. Key in this respect is the so-called demographic dividend, which is the potential economic growth stemming from lower dependency ratios. We use the gravity model to link long-run changes of the demographic dividend to changes in the level of world trade for the 21st century. All the scenarios that we distinguish point towards the same conclusion: Compared to the current situation, North America and Europe will no longer be the center of global trade in 2100 due to their aging populations. In contrast, South Asia and Sub-Saharan Africa will experience a substantial increase in their share of world trade throughout the remainder of this century, while the impact of the demographic drag facing China will be most pronounced around 2060.
Keywords: F10; J11; O11; 330; demographic transition; trade; income; gravity model